Photo-induced structural modification of silk gels containing azobenzene side groups. Issue 16 (3rd April 2017) - Landry, Michael J.; Applegate, Matthew B.; Bushuyev, Oleksandr S.; Omenetto, Fiorenzo G.; Kaplan, David L.; Cronin-Golomb, Mark; Barrett, Christopher J.
Abstract : We demonstrate facile 3D laser patterning of azo dye-modified Bombyx mori silkworm silk 'azosilk'. Written regions fluoresce, and form fluid-filled raised 'micro-blisters', which exhibit a 10-fold photo-softening of this versatile biomaterial. Abstract : Azobenzene modification of Bombyx mori silkworm silk creates a photo-responsive 'azosilk' biomaterial, allowing for 3D laser patterning. Written regions fluoresce, and become fluid-filled raised 'micro-blisters' with a 10-fold photo-softening effect of the modulus. Patterning is facile and versatile, with potential applications as soft tunable materials for dynamic cell guidance and microfluidics.